2015
DOI: 10.1104/pp.15.00187
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Lateral Root Branching Density Improves Drought Tolerance in Maize

Abstract: An emerging paradigm is that root traits that reduce the metabolic costs of soil exploration improve the acquisition of limiting soil resources. Here, we test the hypothesis that reduced lateral root branching density will improve drought tolerance in maize (Zea mays) by reducing the metabolic costs of soil exploration, permitting greater axial root elongation, greater rooting depth, and thereby greater water acquisition from drying soil. Maize recombinant inbred lines with contrasting lateral root number and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(193 citation statements)
references
References 69 publications
(101 reference statements)
8
179
4
2
Order By: Relevance
“…However, these processes may be highly relevant in plants subjected to abiotic stresses. The paradigm that deep rooting is important for drought tolerance of plants was recently questioned (Grieder et al, 2014;Nippert and Holdo, 2015), but large cortical cells in maize roots (Chimungu et al, 2014) and lateral root development (smaller number and increased length) were found to be well correlated with drought tolerance (Zhan et al, 2015). Leaf CO2 assimilation and stomatal conductance were considerably increased in maize lines with large root cortical cells compared to lines with smaller ones (Chimungu et al, 2014).…”
Section: Net Co2 Assimilationmentioning
confidence: 99%
“…However, these processes may be highly relevant in plants subjected to abiotic stresses. The paradigm that deep rooting is important for drought tolerance of plants was recently questioned (Grieder et al, 2014;Nippert and Holdo, 2015), but large cortical cells in maize roots (Chimungu et al, 2014) and lateral root development (smaller number and increased length) were found to be well correlated with drought tolerance (Zhan et al, 2015). Leaf CO2 assimilation and stomatal conductance were considerably increased in maize lines with large root cortical cells compared to lines with smaller ones (Chimungu et al, 2014).…”
Section: Net Co2 Assimilationmentioning
confidence: 99%
“…In corn, it has been shown that greater root length (Ali et al, 2016) and fewer lateral roots (Zhan et al, 2015) lead to an increase in drought tolerance. The size of the root cortex and the amount of aerenchyma are characteristics that are heritable and desirable in corn breeding for drought tolerance (Burton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tests in US fields starved of nitrogen showed 3 that maize with few long lateral roots produced yields more than 30% higher than maize with many short lateral roots. The longlateral-root variety performed even better in a test of drought-like conditions, where it showed a 144% increase in yield 4 . Other research teams are taking different approaches to breeding fertilizer-frugal crops.…”
Section: Magic Beansmentioning
confidence: 99%
“…The ability to grow deep roots is influenced by several factors, including the characteristics of a plant's lateral roots -those that grow out of the main framework of roots. Working in maize, or corn (Zea mays), Lynch found that plants perform better under low-nitrogen conditions 3 and water stress 4 when they have just a few long lateral roots rather than many short ones. This arrangement requires less energy to grow, so plants can invest more resources in aboveground vegetation and developing deep roots that can suck up water and nitrogen.…”
Section: Magic Beansmentioning
confidence: 99%